Nigeria Deep Offshore Inland Basin Production Sharing Contract Acts: Evaluating Contractor's Take - Okoro, Emmanuel E.; Echendu, Joseph; Okoye, Lawrence U.; Sanni, Samuel E.; Orodu, Kale B.; Okoro, Rita I. (International Journal of Energy Economics and Policy, 2021)
Value-focused thinking is often designed to focus our decision on the essential activities that must occur prior to solving a decision problem. This approach was adopted by the Nigerian government in the fiscal legislation for Deep Offshore and Inland Basin Production Sharing Contract (DOIBPSC) Act enacted in 1999 and the subsequent amendment of 2020. One major item of interest in the amended Act is the introduction of royalty by price to enable the government to capture windfall in high oil price spike. This study evaluates the new fiscal regime to ascertain its attractiveness and impact of contractor take. Four features (royalty, cost recovery, tax oil, and profit oil) of the PSC contract terms were used to determine contractor and government takes from the transactions. This study adopted the full range of oil prices captured in the amended DOIBPSC Act in addition to the current market price of oil estimation. Six ranges of oil price ($ 20/bbl, $ 30/bbl, $ 40/bbl, $ 80/bbl, $ 120/bbl, $ 160/bbl) were used to cover the five royalty sliding scales adopted in the amended DOIBPSC and the current oil price during this study which is â‰¤ $ 20/bbl. From the econometric analysis, estimates from the unit root tests revealed that the time series data are mixture of I(0) and I(1) series. The ARDL/bound cointegration test result shows that all the integrated variables are cointegrated at a 5% level. Analysis of the impact of the price sliding royalty regime on the contractors' take shows that in both the long run and the short run, the price sliding (royalty by price) regime had a negative impact on the contractors' take. The short-run impact of the royalty level and the regime change on the contractor's take is high and significantly negative. This is expected as the design of the royalty regime is based on long term benefits. Keywords: Deepwater fiscal system; Royalty regimes; Production sharing contract; Oil and Gas; Long and short run JEL Classifications: P28, O22, O38 DOI: https://doi.org/10.32479/ijeep.11244